CHARGED PION-PRODUCTION IN E+E- ANNIHILATION AT 14,22 AND 34 GEV CM ENERGY - Brandelik, R; Braunschweig, W; Gather, K; Kirschfink, F; Lubelsmeyer, K; Martyn, H; Peise, G; Rimkus, J; Sander, H; Schmitz, D; Trines, D; Wallraff, W; et al. (1982)
The inclusive production of π± mesons in e+e- annihilation has been measured at c.m. energies of 14, 22 and 34 GeV for pion momenta between 0.3 ans 10 GeV/c. The fraction of pions among the charged hadrons is above 90% at 0.4 GeV/c and decreases to about 50% at high momenta. The scaled cross sections ( s β) dσ dx at 14, 22 and 34 GeV as well as the 5.2 GeV data from DASP have a rather similar x dependence. After integration over the x range from 0.2 to 0.6 the cross sections indicate a monotonic decrease with increasing centre-of-mass energy. © 1982.